The Routledge companion to design studies - Sparke, Penny; Fisher, Fiona (Routledge Companions, 2016)
Since the 1990s, in response to dramatic transformations in the worlds of technology and the economy, design - a once relatively definable discipline, complete with a set of sub-disciplines - has become unrecognizable. Consequently, design scholars have begun to address new issues, themes and sub-disciplines such as: sustainable design, design for well-being, empathic design, design activism, design anthropology, and many more.